Decreased locus coeruleus signal associated with Alzheimer’s disease based on neuromelanin-sensitive magnetic resonance imaging technique - Li, Meng; Liu, Shanwen; Zhu, Hongqin; Guo, Zhiwen; Zhi, Yuqi; Liu, Rong; Jiang, Zhen; Liang, Xiaoyun; Hu, Hua; Zhu, Jiangtao (Frontiers in Neuroscience, 2022)
Objective Neuromelanin-sensitive magnetic resonance imaging (NM-MRI) technique was used to detect the changes of the locus coeruleus (LC) signals in Alzheimer’s disease patients (AD), and to analyze its correlation with cognitive function. Materials and methods A total of 27 patients with AD, 15 patients with mild cognitive impairment (MCI), and 25 healthy controls (HC) were examined by NM-MRI technique. ImageJ software was used to measure the LC signals. The locus coeruleus signal contrast ratios (LC-CRs) were calculated, along with the measurement of neuropsychological scales. Results The LC-CRs of AD patients were significantly different from that of HC (p = 0.007, 95% CI: −0.053∼−0.007). However, such significant differences were not observed between MCI and HC (p = 1.000, 95% CI: −0.030∼0.024), AD and MCI (p = 0.050, 95% CI: −0.054∼0.000). Furthermore, a significant positive correlation was identified between LC-CRs and MMSE sub item Drawing (r = 0.484, p = 0.011) in the AD group, MoCA sub item Attention (r = 0.519, p = 0.047) in the MCI group. The area under the curve of LC-CRs in the diagnosis of AD was 0.749 (p = 0.002, 95% CI: 0.618∼0.880), with a sensitivity of 85.2% and a specificity of 56.0%. Conclusion The NM-MRI technique could quantify the pathological degenerations of the LC in AD. Such LC degenerations can be employed to distinguish AD from healthy elderly.